Impact of Albizia Wood (Albizia Chinensis) Adsorbent on the Reduction of Pollutants and Copper in Industrial Wastewater - Yulia Sukmawardani; Siti Jualiah; Cucu Zenab Subarkah; Tri Wahyu Agustina; Ade Yeti Nuryantini; Ida Farida (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2024)
This paper investigated the possibility of using mothball tree wood to absorb copper from industrial wastewater. The adsorbent is made from sawdust, activated with 3N H3PO4 for 24 hours to increase its porosity and surface area, and examined its morphology and microstructure by Scanning Electron Microscope (JEOL-6510A). Pollution abatement experiments were carried out with uncontrollable samples from these three original rivers contaminated by textile, laundry, and industrial revenues. Copper content was determined by Atomic Absorption Spectroscopy (AAS); as well as various parameters such as the dissolved oxygen (DO), BOD5,codconsumed nitrates nitrogen, TDS, and TSS measured. As a result of the adsorption process, a significant reduction of pollutants was achieved. The concentrations of copper in samples reduced to lower than measurable levels or became "trash elements," while initial Cu content turned to 0.017ppm, 0.006ppm, and 0.026ppm. Gains included incorruptible DO rates (54.17% textile)d5 BOD falls by 50.05%, 58.56%, and 68.94%, respectively. COD decreased by 33.33%, 50.00%, and 25.00%. Lower TDS enrolled 3.9%, 12.9%, 57.4% TSS went down to 96.38%, 79.17%, 39.76%. These results illuminate the potential of using Albizia wood as an adsorption medium in wastewater treatment, with pollution reductions evident. Future research can further this by using more advanced analysis methods such as XRD,FTIR, turbidity tests and looking at other natural adsorbent materials for improving water treatment.